Inhibition of protease-activated receptor-2 induces apoptosis in cervical cancer by inhibiting signal transducer and activator of transcription-3 signaling. Issue 3 (March 2019) - Shanshan, Hu; Lan, Xiao; Xia, Li; Huang, Wang; Meifang, Zuo; Ling, Yin
Objective: The present study explored how the inhibition of protease-activated receptor-2 (PAR-2) induced proliferation and apoptosis in cervical cancer in vitro and in vivo . Methods: mRNA and protein expression of PAR2 and signal transducer and activator of transcription-3 (STAT-3) was determined by quantitative real-time PCR and western blotting. The proliferation and apoptosis of cervical cancer cells were assayed by the cell counting kit-8 kit, flow cytometry, and western blotting. The effects of PAR2 inhibition on cervical cancer were also examined in BALB/c nude mice in vivo . Results: SLIGRL-NH2 (SL), a selective PAR-2 agonist, promoted proliferation and inhibited apoptosis of healthy cervical cancer cells and HeLa cells, while the PAR-2 antagonist FSLLRY-NH2 (FS) inhibited proliferation and led to apoptosis. SL also promoted the activation of STAT-3, while FS inhibited it and inhibited cancer growth in vivo . Conclusion: FS inhibited cervical cancer by reducing proliferation and inducing apoptosis by interfering with STAT-3 signaling.